Jacob have I loved - Paterson, Katherine (New York Thomas Y. Crowell, 1980)
Feeling deprived all her life of schooling, friends, mother, and even her name by her twin sister, Louise finally begins to find her identity.
Newbery medal, 1981
Keywords: Twins -- Fiction; Sisters -- Fiction; Identity -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction